Beliefs, myths and taboos of pregnant women about vaginal birth - Aline Souza Campos; Ana Carla Campos Hidalgo de Almeida; Reginaldo Passoni dos Santos (Universidade Federal de Santa Maria, 2014)
Doi: 10.5902/2179769210245 Aims: To know the information that pregnant women have regarding vaginal birth, identify those deriving from beliefs, myths and taboos and verify the consistency of the guidance provided by health professionals about the type of delivery. Method: qualitative exploratory-descriptive research, conducted with 30 pregnant women in a city of Paraná. The information was examined using the methodology of content analysis. Results: from the content analysis, three theme categories emerged: the lack of information of the pregnant women about vaginal birth, the power of beliefs originating from family experiences and core friendships, and the lack of contribution with consistent information by health professionals. Final considerations: the feelings experienced during pregnancy are directly related to the beliefs, myths and taboos of the pregnant woman.